Charlie and the great glass elevator - Dahl, Roald; Blake, Quentin (London : Puffin Books, 1995)
Charlie Bucket, having won Willie Wonka's chocolate factory, has gone to collect his family in the great glass elevator, but things go wrong on the return to the factory and Charlie, his parents, two sets of grandparents, and Mr. Wonka find themselves launched into space.
4.4
3-6.
3-6
Keywords: Bucket, Charlie (Fictitious character) -- Juvenile fiction; Wonka, Willy (Fictitious character) -- Juvenile fiction; Bucket, Charlie (Fictitious character) -- Fiction; Humorous stories; Science fiction; Wonka, Willy (Fictitious character) -- Fiction; Bucket, Charlie (Fictional character) -- Fiction; Humorous fiction; Science fiction; Wonka, Willy (Fictional character) -- Fiction; Outer space -- Juvenile fiction; Outer space -- Fiction; Outer space -- Fiction; Humorous fiction; Science fiction